Постоптимальный анализ одной векторной минимаксной комбинаторной задачи - Емеличев, В.А.; Коротков, В.В.; Кузьмин, К.Г. (Кибернетика и системный анализ, 2011)
Розглянуто векторну мінімаксну комбінаторну задачу з критеріями, що забезпечують найбільшу рівномірність параметрів ефективних рішень. Отримано необхідні та достатні умови п’яти відомих типів стійкості задачі до збурень параметрів векторної цільової функції. This paper considers the vector combinatorial problem with minimax criteria that provide the greatest uniformity of the parameters of efficient solutions. Necessary and sufficient conditions are obtained for five well-known types of resistance of a problem to disturbances of parameters of a vector objective function.